Private Activity in Transport Continued at Peak Levels for Second Year - World Bank (Washington, DC, 2012)
This note states that private activity in transport was strong in 2007, following an upward trend over the last three years. Although lower than in 2006, the number of transport projects with private participation, along with the associated investment commitments, remained at peak levels in 2007, according to just-released data from the Private Participation in Infrastructure Project Database.